Think-Aloud Protocol Analysis in Translation Studies - Kussmaul, Paul; Tirkkonen-Condit, Sonja (TTR)

(untitled) (Association canadienne de traductologie, 1995)
AbstractThink-Aloud Protocol Analysis in Translation Studies: This paper reports on think-aloud protocol (TAP) research in Finland and Germany. It discusses some methodological issues: choice of subjects, TAPs in a language-learning and in a professional context, monologue and dialogue protocols, the use of models provided by psycholinguistics. Two types of processes - successful and less successful ones - are distinguished and specified as to the subjects' comprehension and reverbalisation processes, their focus of attention, decision-making, monitoring, flexibility, creative thinking and attitude toward the task. Some tentative results of the research going on in Germany and Finland are presented. The results are expected to serve as hypotheses for the teaching of translation.